Awareness of the presence of nicotine in the JUUL Brand of e-cigarette among adolescents, young adults, and older adults in the United States. (1st November 2020) - McKeganey, Neil; Russell, Christopher; Haseen, Farhana
Abstract: Nicotine warning labels on e-cigarette products can inform potential consumers that using e-cigarettes can cause addiction. This study examined awareness of the omnipresence of nicotine in the JUUL e-cigarette through a cross-sectional online survey of 4860 adolescents (13–17 years), 3746 young adults (18–24 years) and 5000 older adults (25–99 years) in the United States. Analyses also examined variation in nicotine awareness as a function of age, ownership, and past 30-day frequency of JUUL use. Results indicated fewer than half of JUUL ever-users and fewer than half of past 30-day JUUL users were aware that JUUL e-cigarettes always contain nicotine. Among JUUL ever-users, awareness of the omnipresence of nicotine in JUUL e-cigarettes was significantly lower among adolescents and those who did not personally own a JUUL. Among past 30-day JUUL users, awareness of the omnipresence of nicotine was significantly lower among adolescents and infrequent users (i.e. used on 1–19 of the past 30 days). Results suggest many users of a JUUL, especially youth, non-owners and infrequent users, may be underestimating their risk of becoming addicted to JUUL products, or overestimating their ability to stop using JUUL products whenever they choose. Reasons for low awareness and methods for increasing public awareness of the omnipresence of nicotine in JUUL products are proposed.